Kinetics study for sodium transformation in supercritical water gasification of Zhundong coal. (26th July 2018) - Zhang, Deming; Guo, Liejin; Zhao, Jiuyun; Jin, Hui; Cao, Wen; Wang, Runyu; Wei, Wenwen; Chen, Jia
Abstract: Zhundong coal (ZDC) has attracted much attention due to its high alkali metal content which can lead to a series of problems such as furnace slagging and ash fouling. Supercritical water gasification (SCWG) become a better choice for ZDC coal utilization because of its unique chemical and physical properties. The transformation mechanism of alkali metals during SCWG process was different from conventional ways of coal utilization. Systematic research about it could hardly be found. In this study, ZDC was used to explore sodium transformation mechanism and kinetics during supercritical water gasification under typical conditions. We got four kinds of sodium including the water-soluble fraction (L1), the carboxylic matrix-associated fraction (L2), the macromolecular organic group-associated fraction (L3), and the inorganic silicate mineral fraction (L4) through sequential extraction method after SCWG. A reaction pathway of sodium transformation in supercritical water gasification was proposed. A quantitative kinetic model for describing sodium transformation mechanism was developed. Finally, it was found that, L1 played an important role in catalytic process and mineral in coal weaken the catalytic process by combining with L1. L2 and L3 served as the two important intermediate products in the coal gasification, which explained the catalytic mechanism of sodium. L3 showed better reactivity. Sodium finally tended to deposit in the form of NaSiAlO4 (L4) which was stable and environmentally friendly. All of these could provide basis for high-efficiency utilization of ZDC and the design of a reactor. Highlights: Effect of temperature and residence time on the transformation of sodium was investigated. A reaction pathway of sodium transformation was proposed. A quantitative kinetics model was developed. The catalytic mechanism of sodium was revealed. Sodium tended to deposit in the form of sodium aluminosilicate.